Determinasi Ekologis, Growth Mindset, dan Adaptabilitas Karier: Membedah Kecemasan Masa Depan Mahasiswa Perguruan Tinggi Islam - Arham, Abd. Basith; Azizah , Eka Nur (Kartika: Jurnal Studi Keislaman, 2026)
This explanatory-sequential mixed-methods study aims to investigate the intersectional effects of gender and ecological living arrangements on growth mindset and career adaptability, while phenomenologically exploring barriers to vocational transition through the lens of Islamic Clinical Psychology. Quantitative data from 160 final-year students at Islamic higher education institutions in Kediri were analyzed using Pearson correlation and Two-Way ANOVA. Simultaneously, qualitative data from open-ended questionnaires were examined using thematic analysis to extract underlying psychological phenomena. A robust positive correlation exists between growth mindset and career adaptability (r = .646). Crucially, the Two-Way ANOVA revealed a significant disordinal interaction between gender and living arrangements (p = .006). For males, spatial autonomy triggered a 'survival syndrome' that enhanced adaptability, whereas residing at home created a 'comfort zone trap'. Conversely, for females, home provided a vital 'secure base', while independent living within pesantren structures triggered 'future anxiety' and a 'bubble effect'. Qualitative findings highlighted a 'cognitive blindness' among santri (boarding school students), who felt inferior despite possessing high-level transferable skills derived from traditional khidmah and musyawarah practices. Career adaptability is not solely dictated by individual mindset but is deeply ecological and gendered. Conventional career guidance is inadequate; thus, this study highlights the urgency of designing psychospiritual interventions rooted in indigenous psychological capital to help students translate their latent traditional competencies into professional resilience.